Correlation between Escherichia coli and limnological variables in water samples of the Lagoa da Maraponga, Fortaleza, Ceará State, Brazil - doi: 10.4025/actascibiolsci.v33i2.7842 (Acta Scientiarum. Biological Sciences, 2011)
The present work examined possible relationship between the Escherichia coli counts and the concentrations of free CO2, dissolved oxygen, reactive phosphorus, total ammonia, nitrite, pH, transparency and electric conductivity in water samples from the Lagoa da Maraponga (Fortaleza, Ceará State). Eight samplings were carried out every fifteen days to take samples under the water’s surface at three sampling stations. Regression analyses were performed with the variable with the greatest Pearson coefficients searching for the best fitted curve to observed data. The correlation between the water pH and E. coli was best represented by the equation ŷ = 7.63 – 2.92 * 10-4 x (r² = 0.53; P = 0.06) where x is the E. coli count (MPN 100 mL-1) and y is the water pH. We concluded that the inflow of sewage and other affluent rich in organic matter decreases the lake's alkalinity and make it susceptible to the acidification process.